Cytotoxic effects of dose dependent inorganic magnesium oxide nanoparticles on the reproductive organs of rats - Ghada H. Naguib; Gamal S. Abd El-Aziz; Rayyan A. Kayal; Abdulghani I. Mira; Maher S. Hajjaj; Hisham A. Mously; Mohamed T. Hamed (Annals of Medicine, 2023)
AbstractIntroduction Magnesium oxide nanoparticles (MgO NPs) have a variety of applications that have contributed to their elevated popularity, however, the safety and toxic effects on humans are also of concern with these increased applications. There is insufficient data regarding the effect of MgO NPs on reproductive organs, which are crucial aspects to the body’s vital physiological functions. The present study was undertaken in male and female rats to assess the reproductive toxicological potential of two doses (low versus high) of MgO NPs on testicular and ovarian tissues. The toxicity was evaluated using histological, hormonal, and oxidative parameters.Material and Methods In this work, magnesium oxide nanoparticles (MgO NPs) were synthesized by the sol-gel route and were characterized by X ray diffraction analysis (XRD) and Fourier transform infra-red spectroscopy (FTIR). Forty-eight adult Wister albino rats were used in this experiment which were divided into groups of male and female, and then further into control, low dose MgO NPs, and high dose MgO NPs. The low dose used was 131.5 mg/kg b.w. (1/10 LD50) while the high dose used was 263 mg/kg b.w. (1/5 LD50). All doses were given orally by gastric tube. After 4 weeks, blood samples were collected to investigate the level of sex hormones and both ovarian and testicular tissues were examined for variable oxidative parameters and histopathological changes by light microscopy.Results The obtained findings showed that high dose of MgO NPs produced considerable changes in sex hormones and stress parameters in both male and female rats in comparison to the low dose and control groups. Histomorphometric analysis demonstrated the presence of histopathological alterations in the testicular and ovarian tissues.Conclusion The results of this study showed dose-dependent adverse effects of MgO NPs on the testis and ovary both functionally and histopathologically as compared to the control rats.